2004
DOI: 10.1038/nsmb747
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of cooperative RNA binding by the La motif and central RRM domain of human La protein

Abstract: The La protein is a conserved component of eukaryotic ribonucleoprotein complexes that binds the 3' poly(U)-rich elements of nascent RNA polymerase III (pol III) transcripts to assist folding and maturation. This specific recognition is mediated by the N-terminal domain (NTD) of La, which comprises a La motif and an RNA recognition motif (RRM). We have determined the solution structures of both domains and show that the La motif adopts an alpha/beta fold that comprises a winged-helix motif elaborated by the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
181
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(189 citation statements)
references
References 49 publications
3
181
1
4
Order By: Relevance
“…Notably, no matches to other proteins with classical wHTH motifs and reported RNA-binding properties were found among the top hits in the structural similarity search 7 . However, to date only few such proteins have been described, displaying diverse RNA recognition modes [11][12][13][14][15][16] . Among these, the selenocysteine tRNA-specific elongation factor SelB is the single example of a wHTH-containing protein recognizing stem-loop mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, no matches to other proteins with classical wHTH motifs and reported RNA-binding properties were found among the top hits in the structural similarity search 7 . However, to date only few such proteins have been described, displaying diverse RNA recognition modes [11][12][13][14][15][16] . Among these, the selenocysteine tRNA-specific elongation factor SelB is the single example of a wHTH-containing protein recognizing stem-loop mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Expression and purification protocols of La NTD, encompassing residues 1-194, were carried out as reported previously (Alfano et al 2004). NMR samples contained 0.2-0.4 mM of doubly labelled apo protein in 20 mM TrisHCl, 100 mM KCl, 1 mM DTT, 10% D 2 O, pH 7.…”
Section: Methods and Experimentsmentioning
confidence: 99%
“…NMR and X-ray revealed that the 3 0 -poly(U) recognition by La NTD is synergistically mediated by the La domain, an atypical member of the winged helix-turn-helix family, and the RRM; furthermore, this interaction involves structural motifs which are not the canonical nucleic acid binding surfaces in both classes of proteins, highlighting a novel mode of interaction with RNA ligands (Alfano et al 2004;Curry and Conte 2006;Teplova et al 2006).…”
mentioning
confidence: 99%
“…La can shuttle between the nucleus and cytoplasm upon cellular stress (Baboonian et al, 1989;Bachmann et al, 1990). Cytoplasmic La promotes translation of a large variety of viral (Meerovitch et al, 1993;Chang et al, 1994) and cellular RNA (Kim et al, 2001;Holcik et al, 2003) through internal ribosome entry sites because of its modular structure (Trotta et al, 2003;Alfano et al, 2004;Dong et al, 2004). The fact that La is also able to facilitate translation of other mRNAs containing a 5 0 -UTR terminal oligopyrimidine element encoding ribosomal and translation relatedproteins (Crosio et al, 2000;Meyuhas, 2000;Cardinali et al, 2003) suggests a key role for La in mRNA translational regulation and makes La a potential candidate for the recruitment of oncogenic mRNAs to polysomes.…”
Section: Introductionmentioning
confidence: 99%